Natural killer T cell sensitization during neonatal respiratory syncytial virus infection induces eosinophilic lung disease in re-infected adult mice - Lee, Seung Young (PLoS One, 2017)
Respiratory syncytial virus (RSV) is a major viral pathogen that causes severe lower respiratory tract infections in infants and the elderly worldwide. Infants with severe RSV bronchiolitis tend to experience more wheezing and asthma in later childhood. Because invariant natural killer T (iNKT) cells are associated with the asthma pathology, we investigated whether neonatal iNKT cells are involved in the aggravation of pulmonary diseases following RSV infection in mice. Intranasal exposure to the iNKT cell ligand α-galactosylceramide (α-GC) with RSV primary infection in neonatal mice elicited neither cytokine production (except for a slight increase of IL-5) nor pulmonary eosinophilia, despite the presence of both CD1d(+) cells and NKT cells. Interestingly, in adult mice re-infected with RSV, neonatal iNKT cell sensitization by α-GC during RSV primary infection resulted in much higher levels of pulmonary Th2 cytokines and elevated eosinophilia with airway hyperresponsiveness, whereas this was not observed in cd1d knockout mice. In contrast, α-GC priming of adults during RSV re-infection did not induce more severe airway symptoms than RSV re-infection in the absence of α-GC. α-GC co-administration during RSV primary infection facilitated RSV clearance regardless of age, but viral clearance following re-infection was not iNKT cell-dependent. This study clearly demonstrates that RSV-induced immune responses can be altered by iNKT cells, suggesting that neonatal iNKT cell sensitization during RSV primary infection is associated with exacerbation of pulmonary diseases following RSV re-infection in adulthood.